STUDY THE EFFECTIVENESS OF MODIFIED LEVOFLOXACIN (MOLE) ON GRAM NEGATIVE BACTERIA ISOLATED FROM CHILDREN STOOL - Hussein Ali Khayoon; Taisir Abdulelah Kadhim; Mohammed Khaleel Turab; Ahmed Adnan (Scholar Express Journals, 2022)
It is a medication available as tablet, solution, and fluid formulations for the eyes (eye drop). It is commercially available as tablets, oral solutions, and injections. It is rapidly and completely absorbed following oral administration, with the same plasma absorption profile observed following intravenous administration for the same duration. [1-2]. LF has broad antimicrobial activity against numerous gram-positive and gram-negative bacteria. It functions by inhibiting bacterial topoisomerase IV and DNA gyrase, enzymes required for DNA replication, repair, transcription, and recombination. [2].  LF Overdose symptoms include disorientation, dizziness, slurred speech, drowsiness, nausea, vomiting, muscle issues, nerve damage, behavioral changes, or severe mood changes or hypoglycemia. Rarely, LF can cause aorta damage, which can result in life-threatening bleeding or death. [3].             Campylobacter jejuni is the leading cause of gastroenteritis in children and adults. It can occasionally cause systemic infection in children and the elderly. They are gram-negative bacteria, bacilli, and fussy bacteria that require a nutrient-rich medium, are microaerophiolic, and require high CO2 levels. Campylobacter jejuni has a generation time (GT) of between 48 and 72 hours [4]. In infants and young children with compromised immune systems, infections of the stomach and intestines, bareraemia, meningitis, response arthritis, Tpitis, Sepsis (infection in patients with HLA B27), Guillain-Barre syndrome, endocarditis, and inflammatrybwel Miller-Fisher disorder are significantly more severe. [5]. Due to the self-limiting nature of campylobacteriosis, fluoroquinolone or macrolide antibiotics are typically prescribed to patients with persistent symptoms. [6]. However, Campylobacter is becoming more resistant to these essential antibiotics, specifically fluoroquinolones. [7]. As a result, resistance to two essential anti-Campylobacter drugs, ciprofloxacin (fluoroquinolone) and azithromycin (macrolide), has increased, resulting in 310,000 untreatable infections and 28 annual deaths in the United States. [8].
Keywords: Eye drop, Campylobacter drugs, ciprofloxacin (fluoroquinolone) and azithromycin (macrolide),